A systematic review of the effects of nanoplastics on fish - Dasmahapatra, Asok K.; Chatterjee, Joydeep; Tchounwou, Paul B. (Frontiers in Toxicology, 2025)
The global concern about plastics has been amplified due to their widespread contamination in the environment and their ability to cross biological barriers in living organisms. However, our understanding of their bioaccumulation, toxicity, and interaction with other environmental pollutants remains limited. Plastics are classified into three categories: macro-(MAP > 5 mm), micro-(MIP, <5 mm), and nanoplastics (NAP≤ 100 nm). Among these, NAPs have superior sorption capacity, a large surface area, and a greater ability to release co-contaminants into tissues, resulting in more complex and harmful effects compared to MAPs and MIPs. To assess the toxic effects of NAPs, particularly their genotoxicity in fish, we carried out a bibliographic search in PubMed using the search terms “nanoplastics” and “fish,” which yielded 233 articles. These studies focused on various polymers including polyamide (PA), polycarbonate (PC), polyethylene (PE), polyethylene terephthalate (PET), polymethylmethacrylate (PMMA), polypropylene (PPP), polystyrene (PS), and polyvinyl chloride (PVC). We further refined our search by including fish species such as common carp, fathead minnows, medaka, tilapia, trout, and zebrafish and selected 114 articles for review. This article provides a comprehensive overview of the current state of knowledge on the effects of NAPs on fishes, emphasizing their interaction with co-contaminants including metals, polycyclic aromatic hydrocarbons, pharmaceuticals, pesticides, antibiotics, plastic additives, and endocrine disruptors found in the aquatic environments. Our findings indicate that among fish species, zebrafish (∼68%) is the most frequently studied, while PS (∼89%) is the most commonly encountered NAP in the aquatic ecosystems. Despite substantial experimental variability, our systematic review highlights that NAPs accumulate in various tissues of fish including the skin, muscle, gill, gut, liver, heart, gonads, and brain across all developmental stages, from embryos to adults. NAP exposure leads to significant adverse effects including increased oxidative stress, decreased locomotor and foraging activities, altered growth, immunity, lipid metabolism, and induced neurotoxicity. Furthermore, NAP exposure modulates estrogen–androgen–thyroid–steroidogenesis (EATS) pathways and shows potential intergenerational effects. Although the USEPA and EU are aware of the global impacts of plastic pollution, the prolonged persistence of plastics continues to pose a significant risk to both aquatic life and human health.